Pro iOS5 tools Xcode instruments and build tools - Alexander, Brandon; Dillion, Brad; Kim, Kevin Y (Apress, 2011)
Building on your knowledge of how to write basic applications, Pro iOS 5 Tools: Xcode, Instruments and Build Tools shows how to take your apps from promising to real, and from good to great, by using numerous performance and debugging techniques and tools found in Xcode, Apple's Integrated Development Environment (IDE), Interface Builder and more. You will start by studying an alpha-stage iOS app and learning how you can use the tools provided in the iOS developer's toolbox, plus popular third-party tools, to take an app to a final product and ready to ship. Your own app development will never be the same again! Learn the tools available to all iOS developers: Xcode, Instruments, network diagnostic tools and version control Techniques for debugging by using Instruments, as well as the new features available in newest version of Xcode Performance tuning techniques and workflow enhancements